The Nexus between Economic Freedom and Economic Growth in the Least Developed Countries. An Empirical Analysis for the Period of 2000-2021 - Afonso, António; Blanco-Arana, María del Carmen (My University, 2024)
Economic freedom is the fundamental right of every human to control his or her own labour and property, and therefore it constitutes the essence of the market economy. In this sense, economic freedom leads to economic growth and although economic freedom can have an impact on economic growth, it is necessary to specify those aspects of freedom that can foster growth. This paper examines the nexus between economic freedom and economic growth in the Least Developed Countries (LDCs), using panel data for the period of 2000-2021. In particular, we investigate the effects of economic freedom on economic growth in the LDCs by using the 12 dimensions of the economic freedom index published by the Heritage Foundation. Accordingly, this study investigates the potential effects of freedom on growth, revealing that economic freedom is a growth stimulus factor and although not all pillars are determinants of growth in the LDCs, the significance of economic freedom as a whole is crucial. By using different estimation methods (Fixed effects model and Principal Component Analysis), we confirm that economic freedom influences growth in the LDCs. Furthermore, certain variables related to financial development, political stability, capital formation and education, are key for attaining economic growth in these countries.
Keywords: Desarrrollo económico y social; economic freedom; economic growth; LDCs; financial development; panel data